Investigação da relação entre disclosure, materialidade e origem legal dos países: um estudo de transações com partes relacionadas - Holanda, Sandra de Souza Paiva (2015)
This study aims to analyze the relationship between the level of compliance and the disclosure requirements envisaged by IAS 24 - Related Parties, the materiality of the information and the legal origin of countries. To this end, we studied the hundred largest companies in Brazil listed on BM&F Bovespa; the enterprises in continental European countries, listed in the European Union purse belonging to Stoxx 600 index and the business from England are listed on the London Stock Exchange. All these have published the financial statements using the IFRS accounting standards and conducted related party transactions with the base date on 31/12/2012, with exception for financial and insurance companies as well as those that exchange shares on the New York Stock Exchange, which has a high level of enforcement, they are subject to supervision by the SEC, which totaled a sample of 301 companies. To achieve the overall objectives, the disclosure requirements were identified as defined by IAS 24, it was a metric research. The analysis of companies’ compliance to the disclosure requirements related to TPRs contemplated two different interpretations, the first one represented by disclosure index 1, more stringent, and the second one, represented by disclosure index 2, more tolerant. The survey results suggest that many companies in the sample do not meet fully the disclosure requirements laid down by international accounting standard according to the variations of disclosure indexes of companies. In order to identify the factors accounting by level of compliance of the firms, we studied the disclosure required by IFRS using a multiple regression analysis with level of compliance as dependent variable of disclosure of companies and the materiality of related party transactions measured by the value of assets and the value of shareholders' equity, the legal origin countries, (Common Law and Code Law), as well as control variables Leverage, Profitability and Size as independent variable. As results obtained when we analyzed all the companies in the sample, the study found that only the variable Legal Origin showed positive influence and significant at the 1% level in our regression model, and the other variables were not significant, reason which, there is evidence that when the country is under legal system of Common Law, the companies tend to have greater disclosure. Although, it should be noted that the model had low explanatory power, as among the independent variables only one was significant. Regression analysis was also applied to each region separately, where it found that only companies in Brazil showed a statistically significant variable for the size variable. Thus, that the variable size influences positively and significantly the compliance with IFRS at the level of disclosure requirements for Brazilian companies.